Estimation of Different Soil Properties by Using Reflectance Values of TERRA-ASTER Bands - Basayigit, Levent; Akgul, Mesut; Senol, Huseyin (Asian Journal of Chemistry, 2010)
The aim of this study was to determine the relationship between the soil properties and spectral reflectance values obtained from VNIR, SWIR and TIR bands of ASTER-TERRA. For this purpose, 40 soil samples formed on different landscapes were collected. Soil parameters were analyzed for pH, organic matter, total salinity, lime contents and particle sizes. Coordinates of these samples were overlaid on ASTER data using ERDAS Imagine software. The spectral values of VNIR, SWIR and TIR bands of ASTER-TERRA for total 9 pixel point neighboring to each sample were obtained. To determine the relationship between spectral values and soil properties correlation analysis techniques were developed using statistical software program SAS. Finally, the correlations fitted to soil contents and their highly correlated spectral bands were used to produce maps using supervised classification method showing soil properties. The results showed that there was a good agreement between the reflectance values of soil and their properties. The highest correlation coefficient value was found between silty particle and TIR band 3. Similarly there was a high correlation between organic matter and VNIR-Band 2.